Dating Icelandic glacial floods using a new viscous remanent magnetization protocol - Berndt,T; Muxworthy,AR (Geology, 2017)
A new protocol using the viscous remanent magnetization (VRM) of boulders to date cataclysmic geological events such as tsunamis, glacial floods, and landslides is presented and its performance is assessed against two jökulhlaups (glacial floods) of known age in Iceland. High-intensity jökulhlaups have the ability to break off large boulders from bedrock and emplace and rotate them. These rocks originally carried a remanent magnetization parallel to the geomagnetic field during their formation. After being rotated by the flood, they acquire a VRM parallel with Earth's magnetic field. In continuous thermal demagnetization experiments the unblocking temperature of the VRM can be determined, and subsequent rock magnetic VRM acquisition experiments can be used to establish a relationship between the unblocking temperature and the acquisition time, from which the time since the flood can be determined. The protocol was tested on 44 boulders from 2 historical jökulhlaups in Iceland and found to yield good order-of-magnitude estimates: 72 yr (confidence limits 11–360 yr) versus known 155 yr at the Sólheimajökull jökulhlaup and 290 yr (confidence limits 80–2300 yr) versus known 288 yr for the Kotarjökull jökulhlaup. The method can therefore be a valuable tool for future dating of cataclysmic events.